Extrinsic compression of the right external iliac artery secondary to iliac vein stenting. Issue 5 (17th May 2021) - Subramaniam, Syva Imayan; Fung, Adrian T; Taylor, David C
Abstract: Symptomatic extrinsic compression of the external iliac artery (EIA) is a rare complication of surgical intervention. Previous cases of EIA compression have presented in the postoperative period after orthopedic surgery or vascular stenting. We report a case of right EIA compression postvenous stenting causing acute limb ischemia.